AN APPROACH FOR AUTOMATED ASSERTION GENERATION IN TEMPLATE-BASED RTL COMPILERS - Pavlush S. Margarian (ՀՀ ԳԱԱ հրատ.)
An approach for assertion generation which can be used for functional verification of RTL instances generated by a template-based RTL compiler is presented. The suggested approach provides automatic generation of assertions during a RTL compiler development and maintenance. An application of the approach for specific RTL compilers for illustrating the effectiveness of the approach is presented.
Keywords: Technology